2000
DOI: 10.1200/jco.2000.18.5.1004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Academic Functioning in Survivors of Pediatric Bone Marrow Transplantation

Abstract: The use of BMTs with or without TBI entails minimal risk of late neurocognitive sequelae in patients who are 6 years of age or older at the time of transplantation. However, patients who are less than 6 years of age at the time of transplantation, and particularly those less than 3 years of age, seem to be at some risk of cognitive declines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 16 publications
6
81
2
Order By: Relevance
“…8 Young children have been shown to be more sensitive than older ones to the adverse late effects of SCT, at least regarding growth and neuro-cognitive functions. 22,23 There are no reports on the effect of age at SCT on the subsequent physical performance. A correlation between poorer test results and younger age at SCT was shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…8 Young children have been shown to be more sensitive than older ones to the adverse late effects of SCT, at least regarding growth and neuro-cognitive functions. 22,23 There are no reports on the effect of age at SCT on the subsequent physical performance. A correlation between poorer test results and younger age at SCT was shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Having a small sample size is not unusual in research with this medically vulnerable population faced with poor health, many stressors and high mortality rates. 4 Comparing the outcomes of these survivors with those of their siblings is an asset as it controls for both environmental and genetic variance. Conversely, having the mother complete reports on both survivors and siblings limits the data on questionnaires to maternal perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Although early retrospective studies have reported cognitive and academic deficits in survivors of pediatric BMT, particularly if they received cranial radiation at a younger age, 1,2 more recent prospective studies have found that, in general, survivors of HSCT perform well, cognitively and educationally, or even improve some of their performance 2 years post-HSCT compared with their pre-HSCT performance. 3,4 Moreover, some child characteristics (older age at transplant) and familial factors (older maternal age and less maternal depression symptoms) seem to be associated with better outcomes. 3 It is less clear how survivors' outcomes compare to those of their healthy siblings, who are exposed to the family crisis precipitated by the diagnosis of a lifethreatening illness such as cancer, the intense treatment that culminates in a transplant and related complications.…”
Section: Introductionmentioning
confidence: 99%
“…49 Neurological late complications and cognitive/psychosocial consequences Irradiation delivered to the central nervous system and neurotoxic agents is used in conjunction or before HSCT produce permanent neurological and cognitive sequel, especially in very young children. 5,18 In a prospective longitudinal study, Phipps et al 51 found less neurocognitive sequelae in children who underwent HSCT at an older age, but performed below the age of 3 years carried an increased risk of cognitive defects. Front line treatment of the underlying disease with radio-and/or intrathecal chemotherapy given before HSCT may cause progressive damage of the central nervous system and mental deterioration, leading to neuropsychological symptomatology.…”
Section: Second Malignant Neoplasmsmentioning
confidence: 99%
“…In a large cohort of paediatric patients type of graft (unrelated vs related and autologous), older age and lower socioeconomic status 51 were identified as predictive factors of distress related to health-related quality of life. Recently, Felder Puig et al 54 carried out a longitudinal prospective study on health-related quality of life in paediatric recipients using Pediatric Quality of Life Inventor and Health Utilities Index Mark 2 þ 3 (HUI2/3).…”
Section: Second Malignant Neoplasmsmentioning
confidence: 99%